The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1007/s15010-007-6200-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Long-Term Care Acquired Infections in Nursing and Residential Homes in the Emilia-Romagna Region

Abstract: The prevalence study identified a high prevalence of infected patients in nursing homes in Italy, consistent with observation in other geographic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
(30 reference statements)
0
23
1
2
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24] Most reported UTI as the most common type of infection. 15,16,[19][20][21][22][23] Despite a lower prevalence in our survey compared with overseas surveys, we must interpret the results with caution for a few reasons.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Most reported UTI as the most common type of infection. 15,16,[19][20][21][22][23] Despite a lower prevalence in our survey compared with overseas surveys, we must interpret the results with caution for a few reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of antimicrobial use among participating LTCFs was lower (1.3%) compared with results from other European surveys (2.4-15%) [3,11,[21][22][23]. National result showed that the prevalence of antimicrobial use was lower than the prevalence of infections, thus the overuse of antimicrobials is not common in participating LTCFs.…”
Section: Discussionmentioning
confidence: 52%
“…low priority of infection prevention and control measures) [2]. Recent reports with different methodologies indicated that the prevalence of infections is between 2.6% and 11.3% [3][4]. Because of infections, residents are often treated with antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Auch in anderen europäischen Län-dern ist die fortlaufende Dokumentation und Bewertung von HCAI in Altenpflegeheimen nicht etabliert, und es existieren nur einige wenige Prävalenzstudien zu HCAI in Altenpflegeheimen [11,12,13,14,15]. Zudem war es auch bisher nicht mög-lich, Aussagen über den Gebrauch von Antibiotika zu therapeutischen oder prophylaktischen Zwecken in Heimen zu machen.…”
Section: Originalien Und üBersichtenunclassified
“…Viele diesbezügliche Studien wurden bisher in den USA durchgeführt [1,2,18,19,20,21]. Für Europa existieren hingegen nur wenige entsprechende Prävalenzuntersuchungen [11,12,13,14,15,16]. Auch für Deutschland gibt es nur wenige Studien, die die HCAI-Situation in Altenpflegeheimen beschreiben, und Daten zum dortigen Antibiotikagebrauch sind bisher nicht bekannt [11,22,23,24].…”
Section: Diskussionunclassified